Metabolic syndrome and psychological symptoms in pathological pregnancy - Bjelanović, Vedran; Babić, Dragan, liječnik; Tomić, Vajdana; Martinac, Marko; Tomić, Monika; Kuvačić, Ivan, liječnik (2009)
There are numerous studies that indicate the co-morbidity of a metabolic syndrome and mental disorders. Metabolic syndrome and mental disorders in pregnant women are rarely investigated, especially in pathological pregnancy.To determine a relationship between predisposed factors in pregnancy and the occurrence of metabolic syndrome as well as to determine the occurrence of psychological symptoms and disorders in pregnant women. The tested sample consisted of 162 pregnant women (80 with normal and 82 with pathological pregnancy). For the examination, 3 questionnaires were used: clinical, laboratory, ultrasound and radiological scanning.These women had a greater prevalence of psychological symptoms (p<0.001). Women with pathological pregnancy who are diagnosed with metabolic syndrome showed significantly more psychological symptoms.
4th Croatian congress on psychopharmacotherapy with international participation, Zadar, October 7-10, 2009
Bibliografija: 20 jed
Keywords: Metabolički poremećaj -- Patološka trudnoća -- Psihijatrijski poremećaj